2019
DOI: 10.1158/1078-0432.ccr-19-1651
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tumor Genomic Pathway Alterations Using Broad-Panel Next-Generation Sequencing in Surgically Resected Lung Adenocarcinoma

Abstract: Purpose: The majority of broad-panel tumor genomic profiling has used a gene-centric approach, although much of that data is unused in clinical decision making. We hypothesized that a pathway-centric approach using next-generation sequencing (NGS), combined with conventional clinicopathologic features, may better predict disease-free survival (DFS) in early stage lung adenocarcinoma.Experimental Design: Utilizing our prospectively maintained database, we analyzed 492 patients with primary, untreated, completel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…A study [ 34 ] showed that LINC00857 promoted the progression of LUAD, it regulated the cell proliferation, glycolysis and apoptosis of LUAD cells by targeting miR-1179/SPAG5 axis. Another study showed that LINC00857 regulated the progression of lung cancer through cell cycle regulation [ 35 ], there was also a study indicated that cell cycle, Hippo, TGFβ, and p53 pathway alterations were associated with poor disease-free survival (DFS) in early-stage LUAD [ 36 ], these results consistent with our results that cell cycle and p53 signaling pathway were the predicted pathways. LINC01116 was overexpressed in various tumors, such as osteosarcoma, nasopharyngeal carcinoma and some others [ 37 39 ], another study found that LINC01116 was overexpressed in LUAD tissues and cell lines and suggested that LINC01116 may act as an oncogene in LUAD [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…A study [ 34 ] showed that LINC00857 promoted the progression of LUAD, it regulated the cell proliferation, glycolysis and apoptosis of LUAD cells by targeting miR-1179/SPAG5 axis. Another study showed that LINC00857 regulated the progression of lung cancer through cell cycle regulation [ 35 ], there was also a study indicated that cell cycle, Hippo, TGFβ, and p53 pathway alterations were associated with poor disease-free survival (DFS) in early-stage LUAD [ 36 ], these results consistent with our results that cell cycle and p53 signaling pathway were the predicted pathways. LINC01116 was overexpressed in various tumors, such as osteosarcoma, nasopharyngeal carcinoma and some others [ 37 39 ], another study found that LINC01116 was overexpressed in LUAD tissues and cell lines and suggested that LINC01116 may act as an oncogene in LUAD [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…This allows the generation of comprehensive genetic profiles in one assay, identifying multiple oncogenic alterations missed in previous conventional assays. Recent NGS studies have shown that EGFR mutations and co-mutations appear to influence the prognosis of advanced EGFR -mutated lung cancers [ 12 , 13 , 14 ]; however, there have been only a few targeted NGS analysis studies regarding the prognosis of resected early stage EGFR -mutated lung cancer that focused on recurrence [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…MSK-IMPACT sequencing was performed and analyzed as previously described 46 , 48 . TMB was defined as the fraction of nonsynonymous single-nucleotide or insertion/deletion mutations divided by the length of the coding region (in Mb) sequenced by each panel (0.98, 1.06, and 1.22 Mb in the 341-, 410-, and 468-gene panels, respectively).…”
Section: Methodsmentioning
confidence: 99%